Alat Penepung Umbi Porang di Kampung Bonti Kabupaten Pangkep - Azwar Hayat; Onny Sutreasman; Ahmad Yusran Aminy; Andi Erwin E. Putra; Lukmanul Hakim Arma; Hairul Arsyad; Novriany Amaliyah; Gerard Antonini Durma; Asriadi Sakka (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
Porang is a tuber plant with the Latin name Amorphophallus Muelleri. In some areas of South Sulawesi, this plant is known as Tire. Porang belong to the family Araceae, which is a type of tuber plant that is able to live in various types and soil conditions. Porang plants do not have to get direct sunlight so these plants are easy to find on the sidelines of forest plants, plantations or populated land. The main problem faced by the community of bonti village is that They cannot process porang into flour due to lack of flouring machine and does not have human resources that can operate machines / make flour porang. Based on this problems, We do a community service by applying science and technology in bonti village in the form of technology machines that can turn porang into flour. The flouring mechine used is an FFC-15 type with 3 filters driven by a YC90S-4 Single-phase electric motor of 0.75 kW 1 HP with a maximum rotation of 1400 rpm. The machine and electric motor are connected by a v-belt and pulley on both shafts. The result obtained is an increase in the ability to produce flour reaching 80-100kg per hour according to the level of dryness of people's chips. The economic impact felt by partners is the occurrence of savings in production when using electric motors. Per hour of operation of an electric motor only requires around Rp.1,500 which saves up to 80% compared to the use of gasoline or diesel engines.